Association between sense of coherence and loss of independence or death in older adults: Locomotive Syndrome and Health Outcomes in Aizu Cohort Study - Sho Matsushita; Hajime Yamazaki; Yoshie Yamada; Yusuke Ogawa; Yosuke Yamamoto (PLOS One, 2026)
Background Although sense of coherence (SOC) is a core concept to promote healthy aging, evidence of whether SOC improves loss of independence (LOI) or death is lacking. We aimed to investigate the association between SOC and LOI or death in older adults. Methods We enrolled independent older adults aged 65 years or over from a population-based cohort. SOC was assessed using a three-item SOC scale at baseline. The primary outcome was a composite of LOI (defined by Japanese long-term care insurance certification) or death. We investigated the association of SOC with LOI or death using the Cox proportional hazards model. Results During a median follow-up of 5.8 years, 128 out of 1,661 (7.7%) participants had LOI or death. Lower SOC (per 1 standard deviation [SD] decrease) was associated with a higher risk of LOI or death (adjusted hazard ratio 1.25, 95% confidence interval [CI] 1.07 to 1.46, p = 0.005). Lower SOC (per 1 SD decrease) was associated with a higher risk of death (adjusted hazard ratio 1.24, 95% CI 1.03 to 1.50, p = 0.022) as well. Conclusions Older adults with a lower SOC were more likely to experience LOI or death. Enhancing SOC could promote healthy aging in older adults.